2013
DOI: 10.1111/pai.12086
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between glutathione S‐transferase variants, maternal smoking and childhood wheezing changes with age

Abstract: Children with AA genotype for GSTP1 are at increased risk of early-life wheezing if their mothers smoke, but the effect of maternal smoking on wheezing diminishes with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, few publications have investigated the overall effects of GST variants and ETS exposure on asthma symptoms [ 51 55 ], and whether such effects could be modulated by dietary antioxidant intake has not yet been explored. This was the first study to assess how ETS, low dietary vitamin A intake, and GSTP1 genotype affect asthma symptoms in children.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few publications have investigated the overall effects of GST variants and ETS exposure on asthma symptoms [ 51 55 ], and whether such effects could be modulated by dietary antioxidant intake has not yet been explored. This was the first study to assess how ETS, low dietary vitamin A intake, and GSTP1 genotype affect asthma symptoms in children.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood-onset asthma risk has been shown to differ by GSTM1 genotype in relation to both maternal smoking in pregnancy (55,56) and childhood ETS exposure (57), with effects largely restricted to children with GSTM1 null genotype. Results from other studies have suggested an interaction between GSTP1 rs1695 A (Ile105) is a risk allele for childhood wheeze illness in relation to maternal smoking in early life, with an effect most clearly seen in children who are exposed to maternal smoking (59,60). Most of the studies looking at interactions with GSTM1 and GSTP1 genetic variants have shown a positive finding, but not always in the same direction for GSTP1 (58).…”
Section: Tobacco Smoking Exposurementioning
confidence: 99%
“…G (Gene) x ETS interaction underlying susceptibility to asthma and asthma-related phenotypes have been first evidenced in the context of genome-wide linkage scans [5][6][7] and by association studies with candidate genes including ADRB2 (β2-adrenergic receptor) [8], GSTM1 (Glutathione S-Transferase M1) [9], GSTT1 (Glutathione S-Transferase T1) [9] and GSTP1 (Glutathione S-Transferase P1) [10]. Genetic variants at the 17q21 locus that were detected by a GWAS of childhood asthma [11] were shown to confer an increased risk of early-onset asthma in subjects exposed to early-life ETS first in the French Epidemiological study on the Genetics and Environment of Asthma (EGEA) study [12] and, subsequently, in other studies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%